Characterization of Triatoma infestans (Klug, 1834) (Hemiptera: Heteroptera, Reduviidae) from Residual Foci in the States of Bahia and Rio Grande do Sul, Brazil, Using Geometric Morphology - Peixoto, Solange; Belintani, Tiago [UNESP]; Rocha, Dayse; Fontes, Felipe; Frota, Natália; Galvão, Cleber (MDPI, 2023)
Triatoma infestans is one of the main vectors of Chagas disease in Latin America. Although the species is under control in most Latin countries, it is still necessary to maintain epidemiological surveillance. The present study aims to characterize T. infestans populations from residual foci in Bahia and Rio Grande do Sul, Brazil, comparing them with natural populations in Argentina and Bolivia. For this, we adopt the geometric morphometry of the heads. It is possible to report the morphometric variety of the studied populations. In addition, we show that the size of the heads contributes to the differentiation between populations, while the shape has less power to discriminate groups. Furthermore, we show that some natural populations have morphometric proximity to residual populations, suggesting a relationship between these triatomines. Our data do not support the origin of residual populations but demonstrate the importance of new studies with other techniques to understand the dynamics of distribution and reintroduction of these vectors in Brazilian territory.
Keywords: Chagas disease; geometric morphometric; residual foci; Triatoma infestans